ANALISIS KOMPARATIF MODAL DAN PENDAPATAN PEDAGANG PASAR KEDIRI TABANAN SEBELUM DAN SELAMA PANDEMI COVID-19 - I WAYAN MULA SARJANA; I WAYAN TERIMAJAYA; ANAK AGUNG GEDE PUTRA (Universitas Mahasaraswati K. Mataram, 2022)
The traditional market is the center of the economy where the lower middle class looks for needs and income. The purpose of this study was to determine the capital gap between traders in the Kediri Tabanan market before and during the Covid-19 pandemic, as well as to determine the income gap between traders in the Kediri Tabanan market before and during the Covid-19 pandemic.The method of determining the sample uses a simple random sampling technique, where the number of samples to be taken is 88 traders at the Kediri Tabanan Market. The data analysis technique used was paired t-test.Based on the results of SPSS calculations, the following results were obtained: (1) There were differences in the capital of traders at the Kediri Tabanan Market before and during the Covid-19 pandemic, where the value of t count was greater than t table or 23,018>1,988 and the significance value was less than 5% or 0.000 < 0.05. (2) There is a difference in income for traders at the Kediri Tabanan Market before and during the Covid-19 pandemic, where the value of t count is greater than t table or 21,881 > 1,988 and the significance value is less than 5% or 0.000 < 0.05